Isomeric Diruthenium Complexes Bridged by Deprotonated Indigo in cis and trans Configuration. Issue 1 (12th December 2017) - Chatterjee, Madhumita; Ghosh, Prabir; Beyer, Katharina; Paretzki, Alexa; Fiedler, Jan; Kaim, Wolfgang; Lahiri, Goutam Kumar
Abstract: The doubly deprotonated form L 2− of indigo=H2 L can bind two [Ru(acac)2 ] complex fragments in the cis (1 ) and trans configuration (2 ), as evidenced from crystal structure analysis. While the latter type of N, O; N ', O ' coordination has been observed earlier, for example, with [Ru(bpy)2 ] 2+, leading to two equivalent six‐membered ring chelates, the cis arrangement in1 is observed here for the first time in a dinuclear complex, producing one five‐membered ring chelate with N, N ' coordination and one seven‐membered chelate with O, O ' coordination. The different structures of the isomers result in differing electrochemical and spectroelectrochemical (EPR, UV‐Vis‐NIR) responses for various accessible charge states1 n and2 n, n =–, 0, +, 2+. The associated electronic structures were analyzed by DFT (structures, spin density) and TD‐DFT calculations (electronic transitions), revealing mainly metal‐based reduction but largely indigo ligand‐based oxidation of both neutral precursors. Abstract : Distinctly different : The binding of cis or trans configurated deprotonated indigo with two {Ru(acac)2 } fragments results in an unsymmetrical arrangement with seven‐ and five‐membered chelates in1 or in a symmetrical situation with two six‐membered chelates in2 . Distinctly different structural, spectral and spectroelectrochemical features were observed and calculated.